Kissing may be an important and neglected risk factor for oropharyngeal gonorrhoea: a cross-sectional study in men who have sex with men. (9th May 2019) - Chow, Eric P F; Cornelisse, Vincent J; Williamson, Deborah A; Priest, David; Hocking, Jane S; Bradshaw, Catriona S; Read, Tim R H; Chen, Marcus Y; Howden, Benjamin P; Fairley, Christopher K
Abstract : Objectives: A mathematical model suggested that a significant proportion of oropharyngeal gonorrhoea cases are acquired via oropharynx-to-oropharynx transmission (ie, tongue-kissing), but to date, no empirical study has investigated this. This study aimed to examine the association between kissing and oropharyngeal gonorrhoea among gay and bisexual men who have sex with men (MSM). Methods: MSM attending a public sexual health centre in Melbourne, Australia, between March 2016 and February 2017 were invited to participate in a brief survey that collected data on their number of male partners in the last 3 months, in three distinct categories: kissing-only (ie, no sex including no oral and/or anal sex), sex-only (ie, any sex without kissing), and kissing-with-sex (ie, kissing with any sex). Univariable and multivariable logistic regression analyses were performed to examine associations between oropharyngeal gonorrhoea positivity by nucleic acid amplification tests and the three distinct partner categories. Results: A total of 3677 men completed the survey and were tested for oropharyngeal gonorrhoea. Their median age was 30 (IQR 25–37) and 6.2% (n=229) had oropharyngeal gonorrhoea. Men had a mean number of 4.3 kissing-only, 1.4 sex-only, and 5.0 kissing-with-sex partners in the last 3 months. Kissing-only and kissing-with-sex were associated with oropharyngeal gonorrhoea, but sex-only was not. The adjusted odds for having oropharyngeal gonorrhoea were 1.46-fold (95% CI 1.04 to 2.06) for men with ≥4 kissing-only partners and 1.81-fold (95% CI 1.17 to 2.79) for men with ≥4 kissing-with-sex partners. Conclusions: These data suggest that kissing may be associated with transmission of oropharyngeal gonorrhoea in MSM, irrespective of whether sex also occurs.